Elements of Dialectics in the Works by Naturalists at the Old Vilnius University - Griška, Albinas (Problemos, 1978)
The naive dialectics of the Old University as the inevitable result of natural sciences development (end of 19th and beginning of 20th centuries) is analysed. A number of scientists at the University (J. Sniadecky, E. Sniadecky, M. Oczapowsky, etc.) are found to understand the interdependence and causal conditionality of phenomena, the stagelike development of nature. They realized the objective regularity of natural processes thus being close to the right conception of the essence and motive power of nature dynamics.